Effectiveness of Regional Financial Management: The Role of Information Quality and Human Resources Competence - Muhammad Ilham Ismail; Hamzah Ritchi; Zaldy Adrianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study was to determine the effect of information quality and human resource competence on the effectiveness of regional financial management in regional apparatus organizations in Sumedang Regency. This study uses an explanatory quantitative method. Respondents in this study were financial management employees in 54 regional apparatus organizations, totaling 108 people. The instrument in this study was a questionnaire. Data analysis using SEM-PLS. The results obtained were a positive and significant effect of information quality and human resource competence on the effectiveness of regional financial management in regional apparatus organizations in Sumedang Regency. This study will increase our understanding of the concept of good governance in Indonesia, to increase transparency, accountability, and effectiveness, especially in regional financial management.